A #selfie meritocracy in educator professional development: Generating complacency through self-reflection - Teresa Anne Fowler (Canadian Society for Studies in Education, 2019)
At the cornerstone of professional development for K-12 teachers, there is an emphasis on practices of self-reflection and reflective practice that turn the professional educator gaze inward towards the self. Self-reflection has emerged through the teacher-as-researcher and the teacher-as-reflective-practitioner identities in professional development. However, this looking inward avoids looking at the larger social structures and the ways in which knowledge of the self is built on social constructions of knowledge and a privileged identity that marginalizes and oppresses Others. I argue that this distraction on/from the self creates a meritocracy in professional development. A focus on the inward self allows perpetuations of systemic racism to remain entrenched and unchallenged in schooling, further pushing anti-racist work to the margins and the ideal of the inclusive classroom unobtainable. This paper explores how teacher professional development, with a focus on self-reflective practices, ignores social structures and systemic forms of racism in schooling.